Properties of Portland Cement Concrete Incorporating Basalt-Based Pozzolanic Cement - Khalil, Rana (AUC Knowledge Fountain, 2024)
Over the last decade, the world's population has increased dramatically. Due to this growth, the demand for concrete and Portland cement, in return, have increased. Manufacturing of Portland cement is an energy-intensive process that, alone, contributes to about 8% of global CO2. For decades, efforts have been exerted to reduce the harmful environmental impacts of Portland cement by reducing its use in concrete as well as considering alternate binders that may fully or partially replace it. This study aims to assess the properties of concrete incorporating a novel basalt-based pozzolanic cement. To meet this objective, four sets of concrete mixtures were prepared; each with mixtures of w/c of 0.35, 0.45, and 0.55. The first set had CEM I normal ordinary Portland cement (OPC), the second set was made with a newly produced basalt-based pozzolanic cement CEM II (PPC). The third and fourth sets were prepared to gauge the performance of this cement against commonly known pozzolanic mineral admixtures. Hence, the third set had silica fume (10%), while the fourth set had blast furnace slag (25%) as partial replacement of Portland cement. The experimental program involved fresh and hardened concrete testing as well as durability-related tests. The Fouriar Transform Infrared spectroscopy (FTIR) analysis showed that PPC contains silica, thus, has a pozzolanic potential. Compressive strength test results yielded the highest value for silica mixtures and a lower value for the PPC mixes yet adequate for use in several construction applications. For the durability of concrete, the PPC concrete shows a good resistance for chemical as well as good performance for the Rapid Chloride Permeability Test (RCPT) and water permeability tests when compared with the OPC mixtures. This study is not but a step toward a greener and more sustainable one, without compromising the structural properties.